Analisis Kesalahan Siswa Berdasarkan Newman Pada Materi Statistika Ditinjau Dari Gaya Belajar - Fitni Fitni; Yenita Roza; Maimunah Maimunah (Faculty of Education Universitas Negeri Malang, 2020)
Abstract: Mistakes made by students in working on math problems seen from the pattern of students when completing the questions given. The purpose of this study is to look at junior high school student’s mistakes in working on math problems based on Newman’s error analysis of statistical material in terms of student learning styles. The subject of this study were 25 students of class IX at SMPN 1 Mandau in Bengkalis Regency. Research data were collected using written tests and questionnaires to determine student learning styles. The method used in this research is descriptive qualitative. The results of the study were analyzed based on Newman’s error analysis with indicators of errors in reading, errors in understanding problems, errors in transformation, errors in process skills, and writing answers. Student learning styles are group into divergent, convergent, assimilation and accommodation. Errors in transformation generally made to students with divergent, convergent, and accommodation learning styles. Students with an assimilation learning style make more mistakes in process skills. The error is divide into several errors ranging from inappropriate in giving answers to those who do not provide the answer. Abstrak: Kesalahan yang dilakukan siswa dalam mengerjakan soal matematika terlihat dari pola siswa saat menyelesaikan soal-soal yang diberikan. Tujuan penelitian ini adalah untuk melihat kesalahan siswa SMP dalam mengerjakan soal matematika berdasarkan analisis kesalahan Newman pada materi statistika ditinjau dari gaya belajar siswa. Subjek penelitian ini 25 siswa kelas IX di SMPN 1 Mandau di Kabupaten Bengkalis. Data penelitian dikumpulkan dengan menggunakan tes tertulis dan angket untuk mengetahui gaya belajar siswa. Metode yang digunakan pada penelitian ini adalah deskriptif kualitatif. Hasil penelitian dianalisis berdasarkan analisis kesalahan Newman dengan indikator kesalahan dalam membaca, kesalahan memahami masalah, kesalahan transformasi, kesalahan keterampilan proses, dan kesalahan penulisan jawaban. Gaya belajar siswa dikelompokkan menjadi gaya belajar divergen, konvergen, asimilasi dan akomodasi. Kesalahan dalam transformasi lebih banyak dilakukan oleh siswa dengan gaya belajar divergen, konvergen, dan akomodasi. Siswa dengan gaya belajar asimilasi lebih banyak melakukan kesalahan pada keterampilan proses. Kesalahan tersebut terbagi dalam beberapa kesalahan mulai dari yang kurang tepat dalam memberikan jawaban sampai dengan yang tidak memberikan jawaban.